Pengaruh Modal Sosial Terhadap Kemandirian Anggota Kelompok Tani Padi “Tani Makmur II” Desa Kecapi Kecamatan Tahunan Kabupaten Jepara - Nurhaliza, Nadella; Gayatri, Siwi; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aimed to analyze the effect of social capital on the independence of farmer group members and to describe the characteristics of the social capital of group members. The study was conducted in Kecapi Village, Tahunan District, Jepara Regency in February 2025. The location of the study was determined purposively with 48 respondents. The data used in this study were primary data and secondary data. Data were analyzed using multiple linear regression analysis. The results of the study showed that the network was categorized as high with a percentage of 72.91%, trust was categorized as high at 81.25%, and norms were categorized as high at 85.42%. The independence in the farmer group was categorized as high with a percentage of 89.58%. Based on the multiple linear regression analysis, it was shown that social capital including networks, trust, and norms influenced the independence of members of the Padi Tani Makmur II Farmer Group by 58.5%, while the remaining 41.5% was influenced by other variables not included in this study. The variables that partially influenced the independence of farmer group members were variable X1 (Network) and X3 (Norms), while variable X2 (Trust) did not partially influence the independence of members. Based on the results of the study, efforts were needed to increase cooperation with external parties or stakeholders to enhance independence.